The effectiveness of behavioral activation therapy on the symptoms of depression, rumination, and social-occupational functioning impairment among women with postpartum depression - Zahra Nikandish; Ilnaz Sajjadian (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Postpartum depression is caused by a wide range of factors, and women in their postpartum period are highly vulnerable, either physically or emotionally. The present study aimed to investigate the effects of behavioral activation therapy on the symptoms of depression, rumination, and social-occupational functioning impairment among women with postpartum depression (PPD). MATERIALS AND METHODS: This quasi-experimental research included a pre-test, a post-test, and a one-month follow-up, as well as experimental and control groups. The participants were screened using Edinburgh Postnatal Depression Scale (EDPS) in 2019. The research included 32 women who had visited Isfahan Healthcare Centers. They were selected using convenience sampling and then randomly divided into experimental (16 individuals) and control groups (16 individuals). Both groups answered the following questionnaires before, immediately after, and one month after the intervention: Beck Depression Inventory (BDI), Nelon, et al. Ruminative Response Scale, and Mundt et al. Work and Social Adjustment Scale (WSAS). The experimental group received behavioral activation therapy for nine 90-minute sessions once a week. The data were analyzed using the statistical method of multivariance analysis of covariance (MANCOVA). RESULT: The results showed that behavioral activation therapy had a significant effect on the symptoms of depression (P = 0.001, F = 79.65), postpartum depression (P = 0.001, F = 220.359), rumination (P = 0.001, F = 121.765), and social-occupational functioning impairment (P = 0.001, F = 368.512) among women with postpartum depression. The effects of behavioral activation therapy also lasted in the follow-up stage of the study. CONCLUSION: According to the present research, behavioral activation therapy is an effective method that decreases the symptoms of depression, rumination, and occupational-social functioning impairment among women with postpartum depression. Therefore, behavioral activation therapy could be beneficial to intervention designs and treatment of postpartum depression.